Fabrication and Characterization of (Mo1‐xNix) (Si1‐xAlx)2 (x = 0.025, 0.05, and 0.1) Alloys. Issue 2 (26th September 2015) - Song, Binbin; Xie, Xushuai; Feng, Peizhong; Wang, Zhang; Liu, Zhangsheng; Wang, Xiaohong
Abstract : (Mo1‐ x Ni x ) (Si1‐ x Al x )2 ( x = 0.025, 0.05, and 0.1) alloys were prepared using self‐propagating combustion synthesis from Mo, Si, Al, and Ni powders and subsequently hot‐pressed to achieve a high density of above 96.2%. The combustion products were composed of C11b MoSi2 and C40 Mo(Si, Al)2 . A systematic shift of diffraction peaks of C11b MoSi2 toward low angles was observed, and C40 Mo(Si, Al)2 diffraction peaks became stronger with increase of alloying elements. The solid‐solution softening and toughening phenomena were observed in (Mo1‐ x Ni x ) (Si1‐ x Al x )2 alloys. On increasing x from 0.025 to 0.1, the hardness of the alloys decreased from 9.87 to 8.31 GPa, and the fracture toughness increased from 3.79 to 6.48 MPa m 1/2 .